Logistic and time burdens reported by gynecologic and breast cancer survivors - Allison C. Dona; Aisha Ambo; Patricia Jewett; Katherine Brown; Helen Parsons; Arjun Gupta; Deanna Teoh; Anne Blaes; Rachel I. Vogel (BMC Women's Health)
Abstract Background We assessed the effect of the time requirements of cancer care on other life activities and time burden reduction priorities among breast and gynecologic cancer survivors. Methods A total of 224 participants with gynecologic or breast cancer from two cohort studies completed a cross-sectional survey regarding logistic and time burdens of cancer care. We compared agreement with the importance of minimizing travel time, wait time, and trips to the cancer center as well as whether cancer care visits interfered with other activities (dependent care, chores, leisure activities) by employment, education, cancer type, cancer treatment status, dependent status, rural-urban residence, and income. Results About half (108/217, 49.8%) of participants agreed minimizing time burdens was important. Some agreed that cancer care visits interfered with leisure time (31/215, 14.4%) or impacted their ability to care for dependents (17/215, 7.9% [15.9% among those with dependents, 7/44]). Retired participants, compared to working participants, less often agreed with the importance of minimizing travel time (36.5% [31/85] versus 58.0% [58/100]), trips to the cancer center (34.5% [30/87] versus 58.0% [58/100]), and wait time (35.8% [29/81] versus 56.0% [56/100]). Participants with incomes <$50,000 and those receiving maintenance treatment most often agreed that minimizing wait time was important. Those not working (and not retired or on disability) and those receiving active treatment most often agreed that care interfered with leisure activities. Conclusions Minimizing the time needed for cancer care-related tasks matters to patients, especially to those with lower incomes, receiving treatment, and working. In-depth research among demographically diverse populations is needed to evaluate specific time use patterns within cancer care and their association with objective and subjective burden.